Nanoparticles: Promising Tools for the Treatment and Prevention of Myocardial Infarction - Pan Q (Dove Medical Press, 2021)
Qi Pan,1 Jing Xu,1 Cen-Jin Wen,2 Yu-Yan Xiong,1 Zhao-Ting Gong,1 Yue-Jin Yang1 1State Key Laboratory of Cardiovascular Disease, Department of Cardiology, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 2Department of Cardiology, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of ChinaCorrespondence: Yue-Jin YangState Key Laboratory of Cardiovascular Disease, Department of Cardiology, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of ChinaEmail yangyjfw@126.comAbstract: Despite several recent advances, current therapy and prevention strategies for myocardial infarction are far from satisfactory, owing to limitations in their applicability and treatment effects. Nanoparticles (NPs) enable the targeted and stable delivery of therapeutic compounds, enhance tissue engineering processes, and regulate the behaviour of transplants such as stem cells. Thus, NPs may be more effective than other mechanisms, and may minimize potential adverse effects. This review provides evidence for the view that function-oriented systems are more practical than traditional material-based systems; it also summarizes the latest advances in NP-based strategies for the treatment and prevention of myocardial infarction.Keywords: nanoparticles, myocardial infarction, treatment, prevention